Análise de prática como dispositivo de formação de uma professora alfabetizadora - Zacharias-carolino, Aline Gasparini [UNESP] (2023)
This present study aims to provide a practice analysis of a literacy teacher beginning her career. Based on autoethnographic accounts, the research seeks to identify the knowledge mobilized in the actions proposed in the lesson plan and reflect upon how such knowledge can contribute to the teacher training process. Results reveal that teaching knowledge is intricate, multifaceted, and derives from several sources. Thus, practice analysis represents a critical instrument for teachers training, providing space for socialization and, consequently, improving the work developed in the classroom and in the acquisition of a teaching habitus.